The Effect of Experiential Marketing on Revisit Intention of Agricultural Tourism in Nakhon Ratchasima Province, Thailand - Thongklang, Yodsawadee; Wirotthitiyawong, Nilubon (Journal of Management Science Nakhonratchasima University, 2025)
This study aimed to examine the influence of experiential marketing on revisit intention to agricultural tourism destinations in Nakhon Ratchasima Province. The sample consisted of 385 tourists who had previously visited agricultural tourism sites in the province. Data were collected using a structured questionnaire and analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. Hypothesis testing was conducted through multiple regression analysis. The findings revealed that experiential marketing influenced revisit intention to agricultural tourism destinations in Nakhon Ratchasima. When examined by individual components, it was found that relational experience (β = 0.226), behavioral experience (β = 0.199), emotional experience (β = 0.178), cognitive experience (β = 0.173), and sensory experience (β = 0.151) had statistically significant positive effects on revisit intention at the 0.01 level, respectively